Menopause related hormonal and inflammatory regulation of BCL2-mediated apoptosis in cervical cancer: A Systematic review - Amanda Fransisca Rhevytasari; Arini Widya Risanti; Tatit Nurseta; Safrina Dewi Ratnaningrum; Sutrisno Sutrisno; Agustina Tri Endarti (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Menopause is characterized by a decline in estrogen levels that may alter inflammatory signaling and apoptotic regulation. Dysregulation of apoptosis, particularly involving B-cell lymphoma-2 (Bcl2), plays a critical role in cervical cancer progression. This systematic review aimed to synthesize current evidence on menopause-related hormonal changes and inflammatory mechanisms in regulating Bcl2-mediated apoptosis in cervical cancer. Research Methodology: This systematic review followed PRISMA 2020 guidelines. Literature searches were conducted in October 2025 using PubMed and ScienceDirect. Eligible studies included human and animal research examining menopause-related hormonal status, inflammation, and Bcl2-associated apoptotic pathways in cervical cancer. Risk of bias was assessed using the Cochrane RoB 2 tool for human studies and the SYRCLE tool for animal studies. Due to heterogeneity, data were synthesized narratively. Results: Six studies (2 human, 4 animal) published between 2019 and 2024 were included. Human studies demonstrated menopause-associated inflammatory changes, including elevated cytokines (IL-1α, IL-6, CRP), suggesting a pro-inflammatory environment relevant to apoptosis regulation. Animal studies consistently showed downregulation of Bcl2 and upregulation of pro-apoptotic markers (BAX, caspase-3), indicating mitochondrial apoptosis activation under estrogen-deprived conditions. Quantitative effect measures (e.g., OR, RR) were not consistently reported due to the predominance of mechanistic and preclinical designs. Conclusion: Menopause-related hormonal decline is associated with increased inflammation and modulation of Bcl2-dependent apoptotic pathways in cervical cancer. While preclinical evidence strongly supports a mechanistic link, clinical evidence remains limited. Future translational studies integrating molecular, hormonal, and inflammatory biomarkers are needed to establish clinical relevance.